Complement anaphylatoxins as immune regulators in cancer. (8th April 2014) - Sayegh, Eli T.; Bloch, Orin; Parsa, Andrew T.
Abstract The role of the complement system in innate immunity is well characterized. However, a recent body of research implicates the complement anaphylatoxins C3a and C5a as insidious propagators of tumor growth and progression. It is now recognized that certain tumors elaborate C3a and C5a and that complement, as a mediator of chronic inflammation and regulator of immune function, may in fact foster rather than defend against tumor growth. A putative mechanism for this function is complement‐mediated suppression of immune effector cells responsible for immunosurveillance within the tumor microenvironment. This paradigm accords with models of immune dysregulation, such as autoimmunity and infectious disease, which have defined a pathophysiological role for abnormal complement signaling. Several types of immune cells express the cognate receptors for the complement anaphylatoxins, C3aR and C5aR, and demonstrate functional modulation in response to complement stimulation. In turn, impairment of antitumor immunity has been intimately tied to tumor progression in animal models of cancer. In this article, the literature was systematically reviewed to identify studies that have characterized the effects of the complement anaphylatoxins on the composition and function of immune cells within the tumor microenvironment. The search identified six studies based upon models of lymphoma and ovarian, cervical, lung, breast, and mammary cancer, which collectively support the paradigm of complement as an immune regulator in the tumor microenvironment.